2020
DOI: 10.1371/journal.pone.0236717
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity, relatedness and inbreeding of ranched and fragmented Cape buffalo populations in southern Africa

Abstract: Wildlife ranching, although not considered a conventional conservation system, provides a sustainable model for wildlife utilization and could be a source of valuable genetic material. However, increased fragmentation and intensive management may threaten the evolutionary potential and conservation value of species. Disease-free Cape buffalo (Syncerus caffer caffer) in southern Africa exist in populations with a variety of histories and management practices. We compared the genetic diversity of buffalo in nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…D. Zimmerman 2015). AENP has the lowest genetic diversity of the three relict populations of buffalo in South Africa ( H E = 0.425 – 0.482) 16 , 17 , being lower than both KNP and HiP 16 . In contrast to KNP and HiP, the buffalo populations in AENP and MNP currently harbour no diseases of economic importance and AENP has historically also been disease-free 23 , presumably since the disease outbreaks of the 1890s and 1900s.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…D. Zimmerman 2015). AENP has the lowest genetic diversity of the three relict populations of buffalo in South Africa ( H E = 0.425 – 0.482) 16 , 17 , being lower than both KNP and HiP 16 . In contrast to KNP and HiP, the buffalo populations in AENP and MNP currently harbour no diseases of economic importance and AENP has historically also been disease-free 23 , presumably since the disease outbreaks of the 1890s and 1900s.…”
Section: Introductionmentioning
confidence: 91%
“…Population genetics studies of African buffalo, employing microsatellites and mitochondrial DNA, have found high levels of differentiation between subspecies 12 14 and between populations of the Cape buffalo subspecies ( S. c. caffer ) across Africa 13 , 15 17 . The few buffalo studies employing more modern genetics techniques have focused on disease-related variants and variant discovery, while relying on the cattle genome as reference 2 , 3 , 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations